The health of foreign-born homeless families living in the family shelter system. Issue 3 (10th September 2018) - Polillo, Alexia; Kerman, Nick; Sylvestre, John; Lee, Catherine M.; Aubry, Tim
Abstract : Purpose: Foreign-born families face challenges following migration to Canada that may impact their well-being and lead them to homelessness. Yet, there is limited research on the experience of homelessness in this population. The purpose of this paper is to examine the health of foreign-born families staying in the emergency shelter system in Ottawa, Ontario, Canada, and compare their experiences to Canadian-born homeless families who are also living in shelters. Design/methodology/approach: Interviews were conducted with 75 adult heads of families who were residing in three family shelters. This study focused on mental and physical health functioning, chronic medical conditions, access to care and diagnoses of mental disorders. Findings: Foreign-born heads of families reported better mental health than did Canadian-born heads of families with a significantly lower proportion of foreign-born participants reporting having been diagnosed with a mental disorder. Foreign-born heads of families also reported fewer chronic medical conditions than did Canadian-born heads of families. Research limitations/implications: This study relied on self-reported health and access to healthcare services. Data were drawn from a small, non-random sample. Originality/value: This study is one of the first studies to examine the health and well-being of homeless foreign-born heads of families. Moreover, this paper also focuses on disparities in health, diagnoses of mental disorders, and access to healthcare services between foreign-born and Canadian-born families – a comparison that has not been captured in the existing literature.